Leadership from the margins : women and civil society organizations in Argentina, Chile and El Salvador - Cosgrove, Serena, 1963- (Rutgers University Press, 2010)
Women have experienced decades of economic and political repression across Latin America, where many nations are built upon patriarchal systems of power. However, a recent confluence of political, economic, and historical factors has allowed for the emergence of civil society organizations (CSOs) that afford women a voice throughout the region. "Leadership from the Margins" describes and analyzes the unique leadership styles and challenges facing the women leaders of CSOs in Argentina, Chile, and El Salvador. Based on ethnographic research, Serena Cosgrove's analysis offers a nuanced account of the distinct struggles facing women, and how differences of class, political ideology, and ethnicity have informed their outlook and organizing strategies. Using a gendered lens, she reveals the power and potential of women's leadership to impact the direction of local, regional, and global development agendas.